2017
DOI: 10.1097/md.0000000000005884
|View full text |Cite
|
Sign up to set email alerts
|

Serosurveillance of hepatitis A in a region which adopted the universal mass vaccination

Abstract: Hepatitis A is a common infectious disease worldwide that was endemic in many regions of Southern Italy, such as Apulia region. After a large hepatitis A outbreak occurred between 1996 and 1997, in Apulia an active-free immunization program that was targeted to new-borns and adolescents was started. The aim of this study is to investigate the hepatitis A seroprevalence in the adult Apulian population 18 years after the immunization program introduction, in order to evaluate the risk of new epidemics onset.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
(18 reference statements)
1
9
0
1
Order By: Relevance
“…Consistent with previous serosurveillance data (Chen et al, 2014;Lee et al, 2011;Gallone et al, 2017), a continuous high level and no change in anti-HAV seroprevalence was found for the older population (>30 years of age) in the 2006 and 2014 surveys. This is explained by the fact that these older people were more likely to have been exposed to HAV due to poorer hygiene and sanitation during early childhood, at a time when the disease was endemic in China.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous serosurveillance data (Chen et al, 2014;Lee et al, 2011;Gallone et al, 2017), a continuous high level and no change in anti-HAV seroprevalence was found for the older population (>30 years of age) in the 2006 and 2014 surveys. This is explained by the fact that these older people were more likely to have been exposed to HAV due to poorer hygiene and sanitation during early childhood, at a time when the disease was endemic in China.…”
Section: Discussionsupporting
confidence: 90%
“…Following a large epidemic in 1998, a vaccination program for toddlers and preadolescents was introduced in this region. Consequently, the incidence of disease has dramatically decreased between 2005 and 2014, which could explain our study results [ 43 ]. However, the increase of susceptible subjects and the permanence of environmental and behavioral risk factors may determine the onset of new epidemics in the case of re-entry of the pathogen, as Ajelli et al [ 44 ] theorized through a mathematical predictive dynamic model.…”
Section: Discussionmentioning
confidence: 87%
“…139,145 Similar data were reported for regional UMVs regarding disease incidence, 86,152,154 outbreak frequency, 158 and regarding hospitalizations. 166 Other epidemiological parameters indicating nationwide or regional success or expected effects of UMV were: herd protection of untargeted age groups 22,146,147,149,154,160 (section 4.2), a rise in seroprotection rates in targeted children/adolescents 153 or young adults, 161 susceptibility (seronegativity) shift toward older age groups, 163,172 a disease burden shift toward older age, 154,156,[171][172][173][174] international travel becoming a predominant risk factor for HAV transmission, 171,172 a decline in the rate of infection-induced high anti-HAV levels in non-vaccinated toddlers, 159 a declining rate of HAV among all viral hepatitis cases 151 and finally, declining HAV positivity of river water samples. 144 To sustain HAV elimination, a certain vaccination coverage of the pediatric target population should be maintained.…”
Section: Effect Of Universal Mass Vaccination (Umv) On Disease Burdenmentioning
confidence: 99%